Employee green behavior through the lens of perceived CSR for environment - Rasool, Iffat; Ashraf, Fatima (2024)
Environmental CSR has become an inevitable to attain the organizational sustainability, therefore employees are encouraged to have pro environmental behavior at work as they have a key role to implement the environmental CSR initiatives. This article investigates the relations between Perceived Environmental CSR and Employee Green Behavior through the moderating effect of Green HRM in hotel industry. The data from 469 respondents of five star hotels was analyzed through SEM and AMOS software. The finding of study indicate the positive relationship between hypothesizes and results suggest that having implementation of environmental CSR by the organization have positive impact on in job green behavior of employees. While green HRM practices strengthen this relationship by hiring, training, rewarding the green behavior. If the hotel industry desires to grow it needs to involve environmental strategies through leadership and HRM collaboration.